Temporal‐spatial pattern of organic carbon sequestration by Chinese lakes since 1850. (30th December 2017) - Wang, Mei; Wu, Jianghua; Chen, Huai; Yu, Zicheng; Zhu, Qiu'an; Peng, Changhui; Anderson, Nicholas John; Luan, Junwei
Abstract: In the last century, lakes in China have been subject to forcing by climate change, intensification of agriculture, and urban expansion, though their effects on lake OC sequestration are poorly understood. We compiled dry mass and OC burial rates from 82 210 Pb‐dated lake sediment records in China. The average post‐1950 focusing‐corrected lake mass accumulation rate (MARFC ) of 256 ± 56 g m −2 yr −1 (median ± SE) and focusing‐corrected OC accumulation rate (CARFC ) of 8 ± 3 g C m −2 yr −1 were significantly higher than the 1850–1900 rates ( p  < 0.05). However, the magnitude of increase in CARFC was most marked in the subtropical lakes of the East Plain (EP) and on the Yunnan‐Guizhou Plateau (YG), where the post‐1950 CARFC was about three times that of the 1850–1900 ( p  < 0.05), due to the agricultural intensification and urban expansion in recent decades. Moreover, MARFC was significantly higher in the EP than that on the Mongolia‐Xinjiang Plateau (MX) for all time periods ( p  < 0.05). Lake CARFC in YG was significantly higher than rates in the Qinghai‐Tibetan Plateau (QTP) for the post‐1950 and MX for the 1850–1900 ( p  < 0.05). Regression analyses showed that the controls on lake CARFC varied among regions, with catchment climate variables the most important regulators in MX, Northeast China, and QTP, but the in‐lake nutrient concentrations were more important in YG and EP ( p  < 0.05). The results from this study show how modern limnic OC sequestration has changed with human disturbance and climate change in China.